2015
DOI: 10.5958/2394-4196.2015.00010.2
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Bone Changes in Post-menopausal Osteopenic and Osteoporosis Women: An Original Research

Abstract: Background: Osteoporosis is imposing public health burden especially in postmenopausal women and elderly population. It is leading cause of morbidity and mortality in postmenopausal women. Among multiple modalities of osteoporosis diagnosis, bone mineral density (BMD) is considered as a gold standard by WHO. Aim: Evaluate the alveolar bone changes in osteopenic and osteoporosis condition of postmenopausal women. Materials and Methods: Totally 1315 postmenopausal women were included in this study. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Additionally, Majumder and Harun [9] assessed the alterations in alveolar bone among postmenopausal women with osteopenia and osteoporosis. They found a considerable correlation between the BMD of systemic skeletal bone and alterations in the alveolar bone of postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Majumder and Harun [9] assessed the alterations in alveolar bone among postmenopausal women with osteopenia and osteoporosis. They found a considerable correlation between the BMD of systemic skeletal bone and alterations in the alveolar bone of postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal alveolar bone changes strongly correlate with BMD so that this relationship can be foundational in assisting the diagnosis of osteoporosis patients [32]. BMD changes are substantial at the end of perimenopause and continue to decline rapidly during the early postmenopausal period [29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MCI, mostly linked to age-and osteoporosis-related changes in the mandibular cortical layer, is being evaluated more commonly in postmenopausal women (around the age of 50 years), and with advancing age, MCI category has a tendency to change [23][24][25]. Numerous panoramic radiomorphometric indices of the mandible and their relationships with skeletal bone mineral density as well as subjects' age and gender have been evaluated in different populations [12].…”
Section: Discussionmentioning
confidence: 99%